Stem cell therapy for the treatment of psychiatric disorders: a real hope for the next decades - Villanueva, Rosa (Frontiers in Psychiatry, 2025)
In this review, it is evaluated the progress in the application of stem cell therapy to ameliorate the symptoms of bipolar disorder, major depression, schizophrenia, and autism. These disorders are highly prevalent in clinical medicine and are responsible for high levels of psychosocial disability among patients. All of them share common biomedical features, such as complex and variable genetic substrates, significant susceptibility to environmental changes, and insufficient knowledge of their pathogenesis. In addition, the responsiveness of patients to pharmacological treatment is heterogeneous, and in some cases, no treatment is available. Therefore, the development of stem cell-based regenerative medicine and its possible combination with emerging therapeutic approaches that promote neural plasticity are expected to advance neuropsychiatry in the next few decades.